A critical review of the educational philosophies underpinning Science and Engineering foundation programmes. - Kloot, B.; Case, J. M.; Marshall, D. (South African Journal of Higher Education, 2008)
More than a decade prior to the official dismantling of apartheid in South Africa, a number of universities launched foundation programmes to assist disadvantaged students. This article focuses on science and engineering foundation programmes, locating them within their political and institutional context and then tracing the evolution of their educational philosophy. But foundation programmes only represent one strategy for dealing with educational disadvantage. It is therefore compared to an alternative model explored in the early 1990s which emphasised the 'infusion' of academic development principles into the mainstream. This provides a backdrop for considering the educational effectiveness of the foundation programmes that have recently proliferated as a result of the Department of Education's latest funding strategy.